Main directions of economic development of the republic of Azerbaijan (Economics and region, 2025)
Economic development refers to growth and changrs in the economy of any country. This process can occur in many areas, such as industrial development, expansion of the labor market, and improvements in technology. The min directions of economic development for Azerbaijan are based on different, different priorities. This includes increased investment in industry, energy development, improvements in technology and education. Also, the development of the labor market plays an important role. Having chosen the path of independent and development, the future economic development of Azerbaijan mainly depends on the implementation of appropriate and systematic economic reforms. In addition to these, the state faces the problems of strengthening foreign trade relations and increasing economik efficiency. The resolution of the mentioned matters depends significantly on the expansion of favorable foreign trade relations that are in line with the country`s national interests. In trade relations, based on the achievements of scientific and technical progress, it is required to produce competitive products and services and ensure free access to international markets by using technologie more effectively. In general, determining directions for improving foreign trade relations is of great practical importance. The adoption of new laws in the economic field, the adaptation of Azerbaijan`s economic laws to European standards and other legislaative initiatives not only ensured the national development of our country, but also deepened its integration with the countries of the world and created favorable opportunities for access to European markets. On the other hand, the policy of economic revival and reintegration in the liberated territories has opened a new stage in the economic development of Azerbaijan. In these territories, reconstruction work based on the concepts of "smart village" and "smart city", the use of alternative energy potential and the economic integration of regions are bringing new dynamics to the country's economy. From this point of view, the topic is of great relevance not only from economic, but also from social and geopolitical aspects. Research conducted on this topic makes a valuable contribution to the scientific substantiation of the country's socio-economic policy, the refinement of strategic planning and the formation of a national development concept. Thus, the relevance of the topic "Main directions of economic development of the Republic of Azerbaijan" stems from its theoretical and practical significance, as well as its strategic importance for the future development of the country.
Keywords: division of labor; cost; trade; cooperation; credit; sales; strategy